The Scope of Supervision By The Heritage Over The Use of Assets By Persons Under Guardianship - Fairuszia Carista Syukroini Putri; Iwan Permadi; Arini Jauharoh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The Estates Office (BHP) is a colonial legacy institution that continues to exist in the Indonesian legal system, with the authority to manage inherited assets, oversee guardianships, and implement trusts. This study aims to analyze the BHP's authority in overseeing trusts, the role of notaries and PPATs in supporting the legality of legal actions, and Limitations on the use of assets by guardians for the benefit of those under guardianship. The method used is socio-legal research with a legal and conceptual sociology approach, through a case study at the Surabaya Legal Trust Agency (BHP). The results of the study indicate that BHP has a strategic role as a supervisory guardian to ensure that the guardian carries out its obligations in accordance with the law, protects the rights of parties who are legally incompetent, and prevents abuse of authority. However, the effectiveness of supervision is still hampered by limited human resources, undigitized administrative infrastructure, difficulties in cross-agency coordination, and legal gaps regarding sanctions for negligent guardians. Concrete cases demonstrate negligence by guardians that impacts the fulfillment of the needs of the custodial party, demonstrating the weakness of existing technical regulations. This study emphasizes the importance of reformulating regulations regarding guardianship, strengthening the capacity of BHP, accelerating digitalization, and optimizing inter-agency cooperation to increase the effectiveness of supervision. Thus, BHP can function optimally as a state instrument in providing substantive legal protection for vulnerable parties, while realizing the principles of legal certainty, justice, and benefit.